A retrospective analysis of chemotherapy switch suggests improved outcome in surgically removed, biologically aggressive canine haemangiosarcoma1. (21st January 2016) - Finotello, R.; Henriques, J.; Sabattini, S.; Stefanello, D.; Felisberto, R.; Pizzoni, S.; Ferrari, R.; Marconato, L.
Abstract: Haemangiosarcoma (HSA) has an aggressive biological behaviour and carries a poor prognosis, with less than 10% of treated dogs surviving longer than 1 year. In this retrospective study a varied metronomic chemotherapy (MC) regimen preceded by adjuvant doxorubicin‐based maximum‐tolerated dose chemotherapy (MTDC) was compared with MTDC, in terms of efficacy [time to metastasis, (TTM) and survival time (ST)] and safety in dogs with biologically aggressive HSA. Dogs were eligible if they had no metastasis after MTDC and received either no further chemotherapy or MC maintenance. Twelve dogs received MTDC, and 10 received MC thereafter. Median TTM and ST were significantly longer for dogs receiving MTDC‐MC (not reached versus 150 days, P = 0.028; and not reached versus 168 days, P = 0.030, respectively). Treatment was well tolerated. MTDC followed by MC is safe and suggests improved TTM and ST in dogs with surgically removed, biologically aggressive HSA that are treated in the microscopic setting.